Efektivitas Pemberian Makanan Tambahan (Pmt) Berbahan Dasar Pangan Lokal Terhadap Kenaikan Berat Badan Balita Gizi Kurang (Wasting, Underweight) Di Wilayah Kerja Puskesmas Pelaihari Tahun 2024 - Mardiana Mardiana (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2026)
Background: Malnutrition is a health disorder caused by a lack or imbalance of nutrients needed for growth, thinking activities and all things related to life. According to the South Kalimantan Provincial Health Office, (2023) the results of measurements from South Kalimantan Province in 13 districts showed that 1.01% of toddlers experienced malnutrition and Tanah Laut Regency was ranked 9th with 0.57% of toddlers experiencing malnutrition. Objective: To analyze the effectiveness of Providing Supplementary Feeding (PSF) made from local food on the increase in the weight of malnourished toddlers (wasting, underweight) in the Pelaihari Health Center Work Area in 2024. Method: The research method used in this study is Quasi experiment. The design approach used is one group pretest–posttest design. This study was conducted from July to December 2024 with a total sampling of 70 wasting and underweight toddlers. Results: The results of the Paired Sample T-Test obtained a sign value of 0.001 <0.05 from the average weight of wasting toddlers before PSF, which was 9.1478 kg after receiving PSF to 9.6217 kg while the average weight of underweight toddlers before PSF was 10.3149 kg after receiving PSF to 10.8681 kg. Conclusion: Providing Supplementary Food (PSF) made from local food is effective in increasing the weight of underweight toddlers in the Pelaihari Health Center Work Area in 2024. It is recommended that the provision of Supplementary Food be continued to improve toddler nutrition. keywords: Undernutrition, Provision of Supplementary Food (PSF)